PENGARUH HARGA, PROMOSI, DAN KUALITAS PRODUK TERHADAP MINAT PELANGGAN MEMBELI MOTOR MEREK HONDA CB - Fahmi, Syaifuddin; Ike Ratnasari; Muhammad Hudzaifah (Journal of Innovation Research and Knowledge, 2024)
This research aims to investigate the influence of price, promotion, and product quality on customers' interest in purchasing Honda CB motorcycles. The Honda CB brand of motorcycles serves as a transportation tool that attracts young adults' attention. This study employs a survey method by distributing questionnaires to respondents who are users of Honda CB motorcycles. The number of respondents studied was 104 individuals. The independent variables include price, promotion, and product quality, while the dependent variable is customers' interest in purchasing Honda CB motorcycles. Data analysis was conducted using regression techniques to assess how far these independent variables can predict customers' purchasing interest. The research findings from Bengkel Namikaze indicate that the Price variable is not significant in influencing customers' interest in purchasing Honda CB motorcycles. Furthermore, the findings suggest that the Promotion and Product Quality variables significantly influence customers' interest in purchasing Honda CB motorcycles